THE SYNTHESIS AND NMR SPECTRAL ASSIGNMENTS OF 3-NITRO-4-((6-NITROBENZOTHIAZOL-2-YL)AMINO)-2H-CHROMEN-2-ONE - Dekić, Biljana; Radulović, Niko; Ristić, Milenko; Dekić, Vidoslav (Bulletin of Natural Sciences Research, 2016)
Complete assignment of the 1H and 13C NMR chemical shifts of new coumarin derivate was described in this paper. A new coumarin derivate was synthesized in good yield by reaction of 4-chloro-3-nitrocoumarin and 6-nitrobenzothiazol-2-amine in ethyl acetate in the presence of triethylamine. The complete spectral assignment was achieved using of 1D (1H and 13C NMR) and 2D (1H-1H-COSY, NOESY, HSQC and HMBC) NMR experiments.
Keywords: 2D NMR; 13C NMR; 1H NMR; spectral analysis; synthesis; coumarins